Social Policy and Its Influence on Education in Nigeria: An Empirical Examination of the Safe Schools Programme - Edinoh Kingsley; Odili Chizoba Abigail; Ruth Asemota (Journal of Multidisciplinary Academic Business Studies, 2026)
Purpose: This study aims to examine the influence of the Safe Schools Programme (SSP) as a social policy intervention in creating safe learning environments in Nigerian secondary schools, particularly in contexts affected by insecurity. Research Methodology: A quantitative approach was employed using a simulated cross-sectional survey dataset of 320 respondents, including teachers, school administrators, and community stakeholders, across selected states in northern and central Nigeria. Data were analyzed using descriptive statistics, correlation analysis, and regression modelling. Results: The findings revealed that adequate funding, security infrastructure, personnel training, and community participation significantly contribute to the effectiveness of safe school environments. These factors positively influenced perceptions of school safety and program implementation outcomes. Conclusions: The study concludes that the effectiveness of the Safe Schools Programme depends on strengthening institutional capacity, ensuring sustainable financing, enhancing community-based collaboration, and integrating technology-driven monitoring systems. Limitations: This study is limited by its reliance on simulated cross-sectional data and perception-based measures, which may not fully capture real-time program implementation and long-term impacts. Contributions: This study provides empirical insights into the role of social policy in improving educational safety in insecure environments and offers practical recommendations for enhancing the implementation and effectiveness of the Safe Schools Program in Nigeria.